Aerobic Oxidations via Organocatalysis: A Mechanistic Perspective - Wang, Yongtao; Yao, Jia; Li, Haoran (Synthesis, 2021)
This review focuses on recent advances and mechanistic views of aerobic C(sp3)–H oxidations catalyzed by organocatalysts, where metal catalysis and photocatalysis are not included.1 Introduction2 Carbanion Route: TBD-Catalyzed C(sp3)–H Oxygenation2.1 α-Hydroxylation of Ketones2.2 Carbonylation of Benzyl C(sp3)–H3 Radical Route: NHPI-Catalyzed C(sp3)–H Oxidation3.1 N-Oxyl Radicals and Mechanisms3.2 Oxygenation of Benzyl C(sp3)–H3.3 Solvent Effects4 Hydride-Transfer Route: TEMPO-Catalyzed Oxidations4.1 Oxoammonium Cation and Mechanisms4.2 Dehydrogenation of Alcohols4.3 Oxygenation of Benzyl C(sp3)–H5 Conclusions and Outlook
Keywords: organocatalysis; aerobic oxidation; C(sp3)–H bond; mechanism; hydrogen bond; guanidine; N-oxyl radical